1993
DOI: 10.1021/bp00019a006
|View full text |Cite
|
Sign up to set email alerts
|

NMR and Microelectrode Studies of Hydrodynamics and Kinetics in Biofilms

Abstract: Profiles of flow velocity and dissolved oxygen concentration were studied by NMR and microelectrodes near mixed population biofilms growing on polycarbonate substratum. The profile of dissolved oxygen concentration within the diffusion boundary layer and profiles of flow velocity within the hydrodynamic boundary layer can be described by exponential equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 17 publications
3
60
0
Order By: Relevance
“…Biofilm's efficiency depends on the spatial structure and species' composition of the microbial communities that inhabit them (Davey, O'toole 2000). Both of these items, unless they are violated, ensure the proper functioning of the alive and dead elements of biofilm as a whole, which is consistent with the results of other authors (Lewandowski et al 1993;Moller et al 1996). In water and soil environment under the influence of mineral - nutrients -fertilizers both the quantity and species of microorganisms are in the realignment form that mainly starts growing microorganisms with high nutritional requirements, which are widespread in the environment (Koch 2001).…”
Section: Summary and Discussionsupporting
confidence: 84%
“…Biofilm's efficiency depends on the spatial structure and species' composition of the microbial communities that inhabit them (Davey, O'toole 2000). Both of these items, unless they are violated, ensure the proper functioning of the alive and dead elements of biofilm as a whole, which is consistent with the results of other authors (Lewandowski et al 1993;Moller et al 1996). In water and soil environment under the influence of mineral - nutrients -fertilizers both the quantity and species of microorganisms are in the realignment form that mainly starts growing microorganisms with high nutritional requirements, which are widespread in the environment (Koch 2001).…”
Section: Summary and Discussionsupporting
confidence: 84%
“…A versatile set of these noninvasive NMR techniques has been developed to study chemical and physical properties of small samples (1) and to allow spatial imaging of larger systems (22). Liquid velocity can be determined from spin-lattice relaxation time-weighted NMR data (21), and our determinations have shown that the flow velocity does not reach zero at the biofilm surface (16,17) and that fluid flow can be detected within biofilms (18). These data indicate that convective flow occurs within the water channels (Fig.…”
Section: Physical Probe Datamentioning
confidence: 72%
“…Therefore, the channels are, in essence, the lifeline of the system, since they provide a means of circulating nutrients as well as exchanging metabolic products with the bulk fluid layer (45). For instance, in situ measurements of dissolved oxygen using microelectrodes revealed that oxygen is available in the biofilm as far down as the substrata, indicating that the channels are transporting the oxygenated bulk fluid throughout the biofilm to the surface (143). Also, in situ measurements of toluene degradation in a multispecies biofilm indicated that toluene was available to cells deep within the biofilm, indicating transport through channels (168).…”
Section: Biofilm Structurementioning
confidence: 99%